2015
DOI: 10.1111/bju.13033
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a fixed‐dose combination of dutasteride and tamsulosin treatment (Duodart®) compared with watchful waiting with initiation of tamsulosin therapy if symptoms do not improve, both provided with lifestyle advice, in the management of treatment‐naïve men with moderately symptomatic benign prostatic hyperplasia: 2‐year CONDUCT study results

Abstract: ObjectiveTo investigate whether a fixed-dose combination (FDC) of 0.5 mg dutasteride and 0.4 mg tamsulosin is more effective than watchful waiting with protocol-defined initiation of tamsulosin therapy if symptoms did not improve (WW-All) in treatment-naïve men with moderately symptomatic benign prostatic hyperplasia (BPH) at risk of progression. Patients and MethodsThis was a multicentre, randomised, open-label, parallel-group study (NCT01294592) in 742 men with an International Prostate Symptom Score (IPSS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 32 publications
5
53
1
9
Order By: Relevance
“…An editorial following the report by Belknap [89] has highlighted the need to re-think the safety of these drugs [90]. The following section summarizes preclinical and clinical evidence documenting how finasteride and dutasteride may impair sexual function, including sexual desire, erectile, ejaculation and orgasmic function [23,[91][92][93][94][95].…”
Section: Adverse Effects On Sexual Functionmentioning
confidence: 99%
“…An editorial following the report by Belknap [89] has highlighted the need to re-think the safety of these drugs [90]. The following section summarizes preclinical and clinical evidence documenting how finasteride and dutasteride may impair sexual function, including sexual desire, erectile, ejaculation and orgasmic function [23,[91][92][93][94][95].…”
Section: Adverse Effects On Sexual Functionmentioning
confidence: 99%
“…5α-Reductase inhibitors (5α-RIs) therapy with finasteride or dutasteride and α 1 -adrenergic receptor blockers such as tamsulosin are widely used for treatment of lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) [1,2]. 5α-RIs therapy with finasteride is also widely used for treatment of male pattern hair loss (MPHL), commonly known as androgenetic alopecia (AGA) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…5α-RIs therapy with finasteride is also widely used for treatment of male pattern hair loss (MPHL), commonly known as androgenetic alopecia (AGA) [3,4]. However, one of the main concerns with 5α-RIs therapy is the serious adverse effects on sexual function [1,[5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter, randomized, non-blinded study, that included treatment-naive patients with moderately symptomatic BPH, concluded that a fixed dose of dutasteride/tamsulosin may reduce the risk of clinical progression and improve symptoms compared to expectant treatment, with optional tamsulosin prescription (initiation of protocol-defined therapy if symptoms did not improve). 20 (A)…”
Section: (A)mentioning
confidence: 99%